18.9k views
3 votes
Subtract 2x^2-6x-4

from 4x^2-4x+3
Write your answer in descending powers of x.
Please help lol. im lost

User Frilox
by
4.6k points

2 Answers

1 vote

Answer:

descending powers of x:

Explanation:

User Alf Nielsen
by
5.1k points
3 votes

Answer:

The answer in descending powers of x:

  • -2x²+2x+7

Explanation:

We have to subtract
2x^2-6x-4 from
4x^2-4x+3


4x^2-4x+3\:-\left(2x^2-6x-4\right)

Distribute the Negative Sign


=4x^2-4x+3+-1\left(2x^2-6x-4\right)


=4x^2+-4x+3+-1\left(2x^2\right)+-1\left(-6x\right)+\left(-1\right)\left(-4\right)


=4x^2+-4x+3+-2x^2+6x+4

Combine Like Terms


=4x^2+-4x+3+-2x^2+6x+4


=\left(4x^2+-2x^2\right)+\left(-4x+6x\right)+\left(3+4\right)


=2x^2+2x+7

Thus, the answer in descending powers of x:

  • -2x²+2x+7
User Priyanka Vadhwani
by
4.6k points